Synchronization of the mammalian circadian timing system: Light can control peripheral clocks independently of the SCN clock. (7th August 2015) - Husse, Jana; Eichele, Gregor; Oster, Henrik
<x xml:space="preserve">Abstract</x> A vast network of cellular circadian clocks regulates 24‐hour rhythms of behavior and physiology in mammals. Complex environments are characterized by multiple, and often conflicting time signals demanding flexible mechanisms of adaptation of endogenous rhythms to external time. Traditionally this process of circadian entrainment has been conceptualized in a hierarchical scheme with a light‐reset master pacemaker residing in the hypothalamus that subsequently aligns subordinate peripheral clocks with each other and with external time. Here we review new experiments using conditional mouse genetics suggesting that resetting of the circadian system occurs in a more "federated" and tissue‐specific fashion, which allows for increased noise resistance and plasticity of circadian timekeeping under natural conditions.